Presidential Unilateral Action as a Tool of Voter Mobilization. Issue 1 (5th February 2020) - Kang, Myunghoon
Abstract: I develop a formal model that investigates conditions under which the president acts unilaterally to establish a given policy. The key innovation is that unilateral action is considered a costly tool for voter mobilization. Presidential unilateral action activates voters' constitutional concerns, which increases the cost of voting and leads the president's supporters to abstain. However, it also provides extra expressive benefits of voting to the president's supporters who deeply care about the policy established by the unilateral action. Hence, the president acts unilaterally to establish the policy only if its mobilizing effects outweigh its demobilizing effects. This result implies that the president's unilateral action acquires popular support that can compensate for the lack of its constitutionality. I discuss the possibly benign effects of unilateral action that are conducive to an effective government and argue that it is necessary to account for these effects when making normative judgments about unilateral action.